Teachers’ Competence based on Al-Qur’an and Its relevance to Regulation of the Minister of National Education of the Republic of Indonesia No. 16, 2007 - Zulheri (Nalar: Journal of Pedagogy and Society, 2020)
This Library Research is aimed at finding out the competencies of teachers based on the Qur’anic perspective and its relevance to the Regulation of the Minister of National Education of the Republic of Indonesia No. 16, 2007 about teachers’ competency standards. The data were collected from several books of interpretation relating to the title of research and the verses of Al-Qur’an related to the competency of teachers. In addition, the data were analyzed by applying the approach of thematic methods (Maudhu’i). The results of this research showed that the pedagogic complications that the teacher must have were mentioned in some verses of Al-Qur’an. These verses talk about professional complications that teachers must have and are relevant to Regulation of the Minister of National Education of the Republic of Indonesia No. 16, 2007. Also, Al-Qur’an talked about personal competence of the teacher and the relevance to Regulation of the Minister of National Education of the Republic of Indonesia No. 16, 2007 in QS. Al-Nahl verses 43 and QS. AR-Rahman verses 1-4. The verses describe the personal competencies that are part of the teachers’ personality as the foundation of their performance such as maturity, independence, religious life, family life, creativity, and so on. Furthermore, the verses of Al-Qur’an related to social competence that a teacher must have and relevant to Regulation of the Minister of National Education of the Republic of Indonesia No. 16, 2007 are QS. An-Najm Verse 7, Q.S. al- Ahzâb verse 70, QS. Al-Furqân verses 48 and 63, QS. Al-Hujurat verses 2, 6, 11, 12, 13. While the perspectives of education experts related to the competence of a teacher, which must have the nature of Tawadhu’, teach the known knowledge, know the students' ability, practice the taught knowledge, obey the rules, contribute to the leader and be firm and brave, keep the sanctity of material that is syubhat, teach for the sake of Allah SWT, are not rude, do not insult the students’ upbringing.